Novel mechanisms of tube-size regulation revealed by the Drosophila trachea. - Zuo, L.; Iordanou, E.; Chandran, R.R.; Jiang, L. (Cell and Tissue Research, 2013)
The size of various tubes within tubular organs such as the lung, vascular system and kidney must be finely tuned for the optimal delivery of gases, nutrients, waste and cells within the entire organism. Aberrant tube sizes lead to devastating human illnesses, such as polycystic kidney disease, fibrocystic breast disease, pancreatic cystic neoplasm and thyroid nodules. However, the underlying mechanisms that are responsible for tube-size regulation have yet to be fully understood. Therefore, no effective treatments are available for disorders caused by tube-size defects. Recently, the Drosophila tracheal system has emerged as an excellent in vivo model to explore the fundamental mechanisms of tube-size regulation. Here, we discuss the role of the apical luminal matrix, cell polarity and signaling pathways in regulating tube size in Drosophila trachea. Previous studies of the Drosophila tracheal system have provided general insights into epithelial tube morphogenesis. Mechanisms that regulate tube size in Drosophila trachea could be well conserved in mammalian tubular organs. This knowledge should greatly aid our understanding of tubular organogenesis in vertebrates and potentially lead to new avenues for the treatment of human disease caused by tube-size defects.